Comparison of age-related decline in C57BL/6J and CB6F1J male mice. - Gerald Yu Liao; Christina Pettan-Brewer; Warren Ladiges (PLoS ONE)
Variability in physical resilience to aging prompts a comprehensive examination of underlying mechanisms across organs and individuals. We conducted a detailed exploration of behavioral and physiological differences between male C57BL/6J and male CB6F1J mice across various age groups (4, 12, 20, 24 months). In behavioral assays, C57BL/6J mice displayed superior performance in rotarod tasks but higher anxiety while CB6F1J mice exhibited a decline in short-term memory with age. Grip strength, long-term memory, and voluntary wheel running declined similarly with age in both strains. Examining physiological phenotypes, C57BL/6J mice exhibited lower body fat percentages across ages compared to CB6F1J mice, though cataract severity worsened with age in both strains. Analysis of cardiac functions revealed differences between strains, with worsening left ventricular hypertrophy and structural heart abnormalities with age in CB6F1J mice along with higher blood pressure than C57BL/6J. Lesion scores showed an age-related increase in heart, kidney, and liver lesions in both strains, while lung lesions worsened with age only in CB6F1J mice. This study underscores the validity of behavioral assays and geropathology assessment in reflecting age-related decline and emphasizes the importance of considering strain specificity when using mouse models to study human aging.